Artificial Intelligence and Big Data Based Algorithm to Track Child Abduction and Child Trafficking Patterns Using Sensors - Gagneja, Kunal (2024 Second International Conference on Emerging Trends in Information Technology and Engineering (ICETITE), 2024)
Preventing child abduction is another example of application of Artificial Intelligence, sensors and GNSS. Some of the common crimes against abducted children are already known by mainstream media. AI, GNSS and sensors have shown a potential solution to this problem. GNSS chips are as small as 3 millimeters. Their power consumption is so low that even a solar charger smaller than the smallest nail on human hand can power them. In conclusion, such a device can be easily implemented and hidden with child accessories. It makes it difficult for the kidnapper to detect them. It also ensures speedy and timely delivery of justice for the victim. Different sensors make it easy for the device to detect kidnapping at an early stage. Experiments were done with different sensors in 3D. Various possibilities of power source were also studied. Artificial Intelligence was used to figure out a common pattern related to time, location, vehicle, and transportation of the victims. This data can help to reunite families with their abducted children. Yes, big data was also employed to discover a pattern in child abduction and child trafficking. Comparison was made with already existing technologies.